A gamificação como ferramenta para o ensino e aprendizagem do futsal - Cairrão, Marcos Roberto (2020)
This research aims to develop the theme of technique interrelated to tactical issues in futsal from The Network Educational Technologies (TER). It is part of the Network Educational Technologies Development Research Line. Thinking about technological tools that contribute to sports teaching and learning, helping to understand the modality became the main objective. Gamification can be a significant alternative for the constitution of products aimed at sports education. Therefore, a game called "Futsal Player" was developed. This is a qualitative research, and the methodological application endorsed in Schmitz (2005) contributes to the mapping and media analysis on sports issues that supported the construction of the game. The interpretation of the results happens in a descriptive-analytical way. The game was validated in a class of academics of a Complementary Undergraduate Discipline (DCG) entitled "The Teaching of Futsal Via Moodle" where, unanimously, the students informed that the game has the potential for virtual collaboration, for the real movement realization, bringing attraction and commitment to the user. An increase in the validation of the game with a larger number (N) of participants will be the subject of future appreciations, considering the current pandemic moment.